DETECTING FRAUDULENT FINANCIAL STATEMENT AND PREDICTING CORPORATE BANKRUPTCY - Viola, Viola - (Jurnal KIAFE, 2021)
A negative equity company would likely encounter two financial problems, which are bankruptcy and fraud. This research aims to detect fraud indicators in the financial statements of negative equity companies by using Beneish M-Score and predict the bankruptcy of negative equity companies by using Altman Z-Score. This is a qualitative study with a quantitative type of data that is collected through companies' financial statements. Purposive sampling is applied to determine the research samples. 28 companies with negative equity that is listed on the IDX website are analyzed by using Altman Z-Score and Beneish M-Score. Result shows that the percentage of distress company for manufacturing company in 2015 to 2017 is 87.5% while the non-distress is 12.5%. In 2018, the percentage of distress company is 83.33% while non-distress is 16.67%. However, in 2019, all companies are in distress zone of 100%. The Z-Score for non-manufacturing company shows that in 2015 and 2019 the percentage of distress and non-distress is 50%. While in 2016 and 2018 the percentage of distress company 75% while non-distress is 25%. Lastly, in 2017, the percentage of distress company is 100% with no company in non-distress zone. The percentage of manipulator company for 2015 and 2018 is 78.57%, non-manipulator is 21.43%. While in 2016 the manipulator company is 96.43%, non-manipulator is 3.57%. In 2017, the manipulator company is 89.29%, non-manipulator is 10.71%. As for 2019, the manipulator company is 46.43% and the non-manipulator company is 53.57%. During 2015-2019, 89.29% of companies are in the distress zone, 10.71% of companies are in the non-distress zone. While the rate of manipulator company is 96.43% and non-manipulator company is 3.57%.